2023
DOI: 10.1088/2515-7647/acb249
|View full text |Cite
|
Sign up to set email alerts
|

Lateral resolution enhanced interference microscopy using virtual annular apertures

Abstract: The lateral resolution in microscopic imaging generally depends on both, the wavelength of light and the numerical aperture of the microscope objective lens. To quantify the lateral resolution Ernst Abbe considered an optical grating illuminated by plane waves. In contrast, the Rayleigh criterion holds for two point sources or point scatterers separated by a lateral distance, which are supposed to emit spherical waves. A portion of each spherical wave is collected by the objective lens and results in an Airy d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 36 publications
0
16
0
Order By: Relevance
“…Using FDA-phase, the height value is calculated by interpolating the linear fit at the spatial frequency for which the Fourier magnitude is greatest. In the context of the UFO model, it has been shown that the lateral resolution for interference microscopy can be enhanced by selecting specific Fourier components, rather than using linear phase fitting 32 . However, in this paper, the primary goal is the comparison of different scattering and imaging models, rather than the comparison of reconstruction algorithms.…”
Section: Comparison Of the Measured Profilesmentioning
confidence: 99%
“…Using FDA-phase, the height value is calculated by interpolating the linear fit at the spatial frequency for which the Fourier magnitude is greatest. In the context of the UFO model, it has been shown that the lateral resolution for interference microscopy can be enhanced by selecting specific Fourier components, rather than using linear phase fitting 32 . However, in this paper, the primary goal is the comparison of different scattering and imaging models, rather than the comparison of reconstruction algorithms.…”
Section: Comparison Of the Measured Profilesmentioning
confidence: 99%
“…This result is in good agreement to the results obtained for interference microscopy 26 and can be explained with a local enhancement of the NA combined with a limited field of view through the cylinder. For an explanation of the effect of an improved resolution if only a few periods of the grating are in the field of view we refer to Lehmann et al 36 Generally, the std values obtained for an infinitely extended grating and a grating of finite extent differ. Hence, internal reflections at the grating seem to affect the results.…”
Section: Resultsmentioning
confidence: 99%
“…However, for piecewise continuous diffracting or tilted specular surfaces the intensity distribution in the exit pupil plane is no longer uniform and thus a slightly different 3D transfer function occurs. 18,19 H(q ρ , q z , k 0 ) = q z 2k 0 for q ∈ area 1 ,…”
Section: Three-dimensional Transfer Functionsmentioning
confidence: 99%
“…the minimum value of q z,eval , where the 3D TF is different from zero. 19 The 3D TF introduced so far describes the transfer characteristics of interference microscopes under monochromatic illumination given by the wavenumber k 0 = 2π/λ 0 and the central wavelength λ 0 . However, CSI instruments commonly use broadband light sources such as light emitting diodes (LEDs).…”
Section: Three-dimensional Transfer Functionsmentioning
confidence: 99%
See 1 more Smart Citation